Nitrosative modifications of the Ca2+ release complex and actin underlie arthritis-induced muscle weakness. Issue 10 (22nd May 2014) - Yamada, Takashi; Fedotovskaya, Olga; Cheng, Arthur J; Cornachione, Anabelle S; Minozzo, Fabio C; Aulin, Cecilia; Fridén, Cecilia; Turesson, Carl; Andersson, Daniel C; Glenmark, Birgitta; Lundberg, Ingrid E; Rassier, Dilson E; et al.
Abstract : Objective: Skeletal muscle weakness is a prominent clinical feature in patients with rheumatoid arthritis (RA), but the underlying mechanism(s) is unknown. Here we investigate the mechanisms behind arthritis-induced skeletal muscle weakness with special focus on the role of nitrosative stress on intracellular Ca 2+ handling and specific force production. Methods: Nitric oxide synthase (NOS) expression, degree of nitrosative stress and composition of the major intracellular Ca 2+ release channel (ryanodine receptor 1, RyR1) complex were measured in muscle. Changes in cytosolic free Ca 2+ concentration ([Ca 2+ ]i ) and force production were assessed in single-muscle fibres and isolated myofibrils using atomic force cantilevers. Results: The total neuronal NOS (nNOS) levels were increased in muscles both from collagen-induced arthritis (CIA) mice and patients with RA. The nNOS associated with RyR1 was increased and accompanied by increased [Ca 2+ ]i during contractions of muscles from CIA mice. A marker of peroxynitrite-derived nitrosative stress (3-nitrotyrosine, 3-NT) was increased on the RyR1 complex and on actin of muscles from CIA mice. Despite increased [Ca 2+ ]i, individual CIA muscle fibres were weaker than in healthy controls, that is, force per cross-sectional area was decreased. Furthermore, force and kinetics were impaired in CIA myofibrils, hence actin and myosin showed decreased ability to interact, which could be a result of increased 3-NT content on actin. Conclusions: Arthritis-induced muscle weakness is linked to nitrosative modifications of the RyR1 protein complex and actin, which are driven by increased nNOS associated with RyR1 and progressively increasing Ca 2+ activation.